2016
DOI: 10.9790/0853-1508047378
|View full text |Cite
|
Sign up to set email alerts
|

CT angiography of renal arteries: anatomy, variants and its importance in the living donor.

Abstract: Observations: In 100 (100%) cases that were taken for the study 22 cases (22%) showed variations in the bifurcation and branching of the renal arteries was observed. There was an early bifurcation of the renal artery in 10 cases (45.45%). There was an accessory renal artery bilateral in 12 cases (54.54%). Conclusion: Identification of renal vascular variants is important, especially before laparoscopic donor or partial nephrectomy and vascular reconstruction for renal artery stenosis or abdominal aortic aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…This was in agreement with the findings of Palmieri et al, [20] in Brazilian population. In contrast, Aytac et al, [13] , Tyagi et al, [24] and Venkataramulu et al, [21] found that the diameter of the main RA with additional artery was significantly less than those without additional arteries in Indian population. Venkataramulu et al, [21] reported that when the diameter of the renal artery is found less than 4.5mm, the presence of additional artery is suspected.…”
Section: Discussionmentioning
confidence: 92%
“…This was in agreement with the findings of Palmieri et al, [20] in Brazilian population. In contrast, Aytac et al, [13] , Tyagi et al, [24] and Venkataramulu et al, [21] found that the diameter of the main RA with additional artery was significantly less than those without additional arteries in Indian population. Venkataramulu et al, [21] reported that when the diameter of the renal artery is found less than 4.5mm, the presence of additional artery is suspected.…”
Section: Discussionmentioning
confidence: 92%
“…However, the classic illustration of the renal vasculature, formed by one renal artery and one renal vein, occurs in ≤25% of cases. 1 The increased use of laparoscopic nephrectomy and nephron-sparing surgeries has propelled the necessity for a more comprehensive radiological evaluation of the renal vascular anatomy. 2 Conventional angiography was once considered to be the gold standard for the analysis of renal vasculature.…”
Section: Introductionmentioning
confidence: 99%